2019
DOI: 10.1111/corg.12293
|View full text |Cite
|
Sign up to set email alerts
|

Figureheads or potentates? CEO power and board oversight in the context of Sarbanes Oxley

Abstract: Research question/issue:We depart from studies that separately explore chief executive officers' (CEOs') and boards' effects on firm performance. Instead, we examine the direct relationship between CEO power and firm performance, and how board monitoring, and most importantly, a change in the regulatory environment alter the relationship. As such, our study jointly examines the role of both internal and external corporate governance mechanisms on the relationship between CEO power and firm performance. Researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 166 publications
2
12
1
Order By: Relevance
“…In particular, these works suggest the existence of a substitutive relationship between national institutions and governance mechanisms by showing that corporate governance plays a more important role when national institutions are less efficient (Bruno & Claessens, 2010; Chen et al, 2009; Durnev & Kim, 2005). This result contrasts with the conclusions of studies that showed a complementary relationship between national institutions and governance mechanisms (e.g., Haynes, Zattoni, Boyd, & Minichilli, 2019; Lel & Miller, 2008) and with some M&O studies showing that national institutions and governance mechanisms have complementary effects on firm outcomes (e.g., Renders & Gaeremynck, 2012).…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…In particular, these works suggest the existence of a substitutive relationship between national institutions and governance mechanisms by showing that corporate governance plays a more important role when national institutions are less efficient (Bruno & Claessens, 2010; Chen et al, 2009; Durnev & Kim, 2005). This result contrasts with the conclusions of studies that showed a complementary relationship between national institutions and governance mechanisms (e.g., Haynes, Zattoni, Boyd, & Minichilli, 2019; Lel & Miller, 2008) and with some M&O studies showing that national institutions and governance mechanisms have complementary effects on firm outcomes (e.g., Renders & Gaeremynck, 2012).…”
Section: Discussioncontrasting
confidence: 96%
“…In particular, these works suggest the existence of a substitutive relationship between national institutions and governance mechanisms by showing that corporate governance plays a more important role when national institutions are less efficient (Bruno & Claessens, 2010;Durnev & Kim, 2005). This result contrasts with the conclusions of studies that showed a complementary relationship between national institutions and governance mechanisms (e.g., Haynes, Zattoni, Boyd, & Minichilli, 2019;Lel & Miller, 2008) Capron & Guillén, 2009;Schneper & Guillen, 2004;Van Essen, Strike, Carney, & Sapp, 2015). Finally, our study also invites governance scholars to develop an embedded multiple agency model or an actor-centered institutional perspective to understand key stakeholders' influence on national institutions, governance practices and firm outcomes (Aguilera & Jackson, 2003).…”
Section: National Institutions Governance Mechanisms and Firm Outmentioning
confidence: 74%
“…To gain trust from their boards and shareholders, newly appointed CEOs will be more likely to try to accomplish higher levels of strategic actions, which result in significant changes in their firms, than their longer-tenured counterparts would do (Haynes et al, 2019;McClelland et al, 2012;Sewpersadh, 2019). However, longer-tenured CEOs are more skilled in managerial expertise and have a higher network centrality for obtaining crucial information (El-Khatib, Fogel and Jandik, 2015; Haynes et al, 2017).…”
Section: Ceos' Tenurementioning
confidence: 99%
“…However, longer-tenured CEOs are more skilled in managerial expertise and have a higher network centrality for obtaining crucial information (El-Khatib, Fogel and Jandik, 2015; Haynes et al, 2017). Long-tenured CEOs, with a high level of trust from their boards, will negatively affect their firms' performances since the boards cannot exercise impartial monitoring (Haynes et al, 2019;Sewpersadh, 2019). Therefore it can be argued that a long-tenure CEO has more trust from both the shareholders and the board, which allows the CEO to pursue value-destroying investments that negatively influence the firm's performance.…”
Section: Ceos' Tenurementioning
confidence: 99%
“…Board size is a prominent aspect of board composition. Although there have been competing arguments regarding the strengths and weaknesses of larger boards, the bulk of evidence indicates that larger board provides help to better shape corporate strategy (Goodstein et al, 1994) and also support effective monitoring (Haynes et al, 2019). Once the board size gets larger, we expect that there is going to be more diverse expertise and resources available to the organization (Goodstein et al, 1994).…”
Section: Board Sizementioning
confidence: 99%